2020
DOI: 10.1177/0016986220960453
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Gender Disparities Among High-Achieving Students in Mathematics: An Analysis of the American Mathematics Competition (AMC)

Abstract: Using the test scores of more than 2,250,000 students who participated in the American Mathematics Competitions (AMC) from 2009 to 2019, this study examined the direction and magnitude of the trends in gender disparity in participation and high achievement in self-select mathematics exams. The results of this study indicated that the male to female ratio among the AMC participants increased significantly from 2009 to 2019. The findings also showed an established disparity that favored males for each year and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…As the number of female students exceeds that of males, the value of the function becomes larger than 1, and the disparity favors female students. As the number of male students exceeds that of females, the value of the FMR function becomes smaller than 1, and disparity favors male students (Bahar, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As the number of female students exceeds that of males, the value of the function becomes larger than 1, and the disparity favors female students. As the number of male students exceeds that of females, the value of the FMR function becomes smaller than 1, and disparity favors male students (Bahar, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Disparity index calculations. Many prior studies have used disparity indexes to examine gender gaps in mathematics performances (Bahar, 2021;Ellison & Swanson, 2010;Hyde et al, 1990Hyde et al, , 2008Lindberg et al, 2010;Olszewski-Kubilius & Lee, 2011; J. P. Robinson & Lubienski, 2011). In this study, a simple FMR was reported as a measure of gender disparity and denoted with the FMR index.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations